Industrial Round-Wood Losses Associated with Harvesting Systems in Russia - Yuri Gerasimov; Alexander Seliverstov (University of Zagreb, Faculty of Forestry, 2010)
A field-based study was performed to broaden our knowledge of industrial round-wood (IRW) losses associated with most applicable motor-manual (MM) and fully mechanized (FM) harvesting systems in Russia. Observations were made for five harvesting systems, namely cut-to-length (MM CTL and FM CTL), full-tree (MM FT and FM FT), and tree length (MM TL), during the felling, skidding/forwarding, processing, sorting, and loading operations. Damage to IRW was examined in 15 logging companies in Karelia. There were about 23 400 measured logs in 17 harvesting sites during summer and winter seasons. The damages detected were broken down into four groups: mechanical damage, processing defects, contamination with dirt, and deviations from the desired log dimensions. The results were then compared with the effective quality requirements in a given logging company, and the IRW volume loss was determined in terms of the reject rate and value loss per unit volume in the context of a harvesting system. Mechanical damage (torn and loosened grain, cuts in stemwood, and gouges made by grapples), processing defects (branches, log end splits and cracks) and contamination with dirt were the most frequent types of damage. The MMCTL and FM CTL systems provided the minimum losses (the reject rate was 2% of observed logs and 0.5–0.6 € per m3 of total industrial wood). The FT systems resulted in somewhat lower but still acceptable quality (MM: 4% and € 1.1; FM: 3% and € 0.9). The quality of wood harvested with the MMTL system turned out to be the lowest (5%and € 1.4), especially in the summer season. The total annual losses in IRW value at the companies studied were estimated as 1.0 € per IRW m3 or € 1.8 million.